Thymic stromal lymphopoietin–elicited basophil responses promote eosinophilic esophagitis - Noti, Mario; Wojno, Elia D Tait; Kim, Brian S; Siracusa, Mark C; Giacomin, Paul R; Nair, Meera G; Benitez, Alain J; Ruymann, Kathryn R; Muir, Amanda B; Hill, David A; Chikwava, Kudakwashe R; Moghaddam, Amin E; et al. (Nature medicine, 2013)
Eosinophilic esophagitis (EoE) is characterized by esophageal eosinophilia, but the underlying mechanisms promoting eosinophil accumulation remain unclear. David Artis and his colleagues describe a new mouse model of EoE-like disease. The development of EoE-like disease is dependent on thymic stromal lymphopoietin (TSLP) and basophils, whereas inhibition of TSLP or depletion of basophils attenuates established disease. Moreover, individuals with EoE have increased TSLP expression and basophils in the esophagus, suggesting that the TSLP-basophil axis can be targeted in patients with EoE. Eosinophilic esophagitis (EoE) is a food allergy–associated inflammatory disease characterized by esophageal eosinophilia. Current management strategies for EoE are nonspecific, and thus there is a need to identify specific immunological pathways that could be targeted to treat this disease. EoE is associated with polymorphisms in the gene that encodes thymic stromal lymphopoietin (TSLP), a cytokine that promotes allergic inflammation, but how TSLP might contribute to EoE disease pathogenesis has been unclear. Here, we describe a new mouse model of EoE-like disease that developed independently of IgE, but was dependent on TSLP and basophils, as targeting TSLP or basophils during the sensitization phase limited disease. Notably, therapeutic TSLP neutralization or basophil depletion also ameliorated established EoE-like disease. In human subjects with EoE, we observed elevated TSLP expression and exaggerated basophil responses in esophageal biopsies, and a gain-of-function TSLP polymorphism was associated with increased basophil responses in patients with EoE. Together, these data suggest that the TSLP-basophil axis contributes to the pathogenesis of EoE and could be therapeutically targeted to treat this disease.